PENGARUH KOMPETENSI GURU TERHADAP MOTIVASI BELAJAR SISWA KELAS XI PADA MATA PELAJARAN AKIDAH AKHLAQ DIMA NW TEKO TAHUN PELAJARAN 2024/2025 - Purwati, Nila; Zulkifli, Muh; Komaruddin, Komaruddin (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to describe the effect of teacher competence on learning motivation of grade XI students of Madrasah Aliyah Nahdlatul Wathan Teko in Pringgabaya District, East Lombok Regency in Akidah Akhlak subject. This study aims to describe the effect of teacher competence on learning motivation of grade XI students of Madrasah Aliyah Nahdlatul Wathan Teko in Pringgabaya District, East Lombok Regency in Akidah Akhlak subject. This research is a quantitative study with an expost pacto research design.. The results of hypothesis testing from simple linear regression analysis prove that the value obtained by the equation Y = 12.425 + 0.697 X. Teacher competence has a positive and significant effect on student learning motivation in moral creed subjects by 0.697 and is evidenced by the coefficient of determination (R Square) that student learning motivation in moral creed subjects is influenced by teacher competence by 77.4%. While the remaining 22.6% is influenced by other factors. While the remaining 22.6% is influenced by other factors that do not come from teacher competence in the subject of Akidah Akhlak.